Mathematical model for predicting the ultrasonic pulse velocity of concrete. Issue 1 (31st December 2023) - Moutassem, Fayez; Miqdadi, Issam
Abstract: This paper proposes a mathematical model approach to predict the Ultrasonic Pulse Velocity (UPV) of concrete. This paper presents the formulation, calibration, evaluation, and validation of the proposed UPV model. An experimental program was developed to calibrate and evaluate the proposed model. Furthermore, the model was validated using a separate group of measurements in the experimental program, to test its accuracy and generalization capability. Analysis of the results reveals that the proposed model provides a good fit to the experimental data and does not contain outliers or discerning pattern. The corresponding standard error and determination coefficient are 45 m/s and 0.92, respectively. Model validation demonstrates high predictability and generalization capability. The corresponding standard error and determination coefficient are 74 m/s and 0.91, respectively.